5
$\begingroup$

What I tried :

$$\int \frac {\log x}{\sqrt {1-x^2}} dx$$

$$= \log x \int \frac {1}{\sqrt {1-x^2}} dx - \int \frac{1}{x} \left(\int \frac {1}{\sqrt {1-x^2}} \, dx\right) \, dx$$

Now,

$$\int \frac {1}{\sqrt {1-x^2}} \, dx = \arcsin x + c$$

But inputting this into the $\displaystyle\int \frac{1}{x} \int \left(\frac {1}{\sqrt {1-x^2}} \, dx\right) \,dx$ part is not getting me into a neat solution. Looks like there is some complex solution of the problem, but I don't know how to solve complex integration. What I did is :

$$\int \frac{1}{x} \int \left(\frac {1}{\sqrt {1-x^2}} \, dx\right) \, dx$$

$$= \int y \cot y \, dy \text{ where } y = \arcsin x$$

$$= y \ln |\sin y| - \int \ln |\sin y |dy$$

So will you plz help me in one of the two ways:

  1. $\displaystyle\int y \cot y \, dy = \text{?}$ or $\displaystyle\int \ln |\sin y | \, dy = \text{?}$

  2. Any better/neater solution of the original problem ?

I saw this question in MSE but in definite integral form, (which is okay), but not sure about this indefinite form.Thanks.

$\endgroup$
  • $\begingroup$ Set $x=\sin y$ and use math.stackexchange.com/questions/37829/… $\endgroup$ – lab bhattacharjee Jul 20 '16 at 4:44
  • $\begingroup$ Yes I did $y = \arcsin x$ , I said, also this link again goes back to definite integrals. $\endgroup$ – null Jul 20 '16 at 4:47
  • $\begingroup$ Pulling $\log x$ out of the integral is nonsense, since the integral is with respect to $x$ and $\log x$ depends on $x$. $\qquad$ $\endgroup$ – Michael Hardy Jul 31 '16 at 4:34
  • $\begingroup$ The most important thing here is that if ever anyone was begging for INTEGRATION BY PARTS, this is it. Notice that you can easily differentiate $\log x$, getting $\dfrac d {dx} \log x = \dfrac 1 x$, and you can easily antidifferentiate $\dfrac 1 {\sqrt{1-x^2}}$, getting $\arcsin x$. In integration by parts you have $\displaystyle \int u\,dv$, and you always differentiate $u$ and antidifferentiate $dv$. $\qquad$ $\endgroup$ – Michael Hardy Jul 31 '16 at 4:36
5
$\begingroup$

I do not think that we could find a closed form expression except using very special and complex function.

If $$I=\int \frac {\log (x)}{\sqrt {1-x^2}}dx$$ just as you did using integration by parts $$u=\log(x)\implies du=\frac{dx}x$$ $$dv=\frac {dx}{\sqrt {1-x^2}}\implies v=\sin^{-1}(x)$$ then $$I=\log (x) \sin ^{-1}(x)-\int \frac{\sin ^{-1}(x)}{x}\,dx$$ This last integral could be computed using Taylor series $$\sin^{-1}(x)=\sum^{\infty}_{n=0} \frac{(2n)!}{4^n (n!)^2 (2n+1)} x^{2n+1}\quad\text{ for }|x| \le 1$$ which makes, integrting each term of the expansion, $$\int \frac{\sin ^{-1}(x)}{x}\,dx=\sum^{\infty}_{n=0} \frac{(2n)!}{4^n (n!)^2 (2n+1)^2} x^{2n+1}$$

Just for your curiosity, this last summation corresponds to $$\int \frac{\sin ^{-1}(x)}{x}\,dx=x \,\, _3F_2\left(\frac{1}{2},\frac{1}{2},\frac{1}{2};\frac{3}{2},\frac{3}{2};x^2\right )$$ where appears the generalized hypergeometric function.

What is amazing (at least to me !) is that this monster is quite "close" to $\frac{\pi \log (2)}{2}x $.

Edit

Another possible way is to start with the expansion $$\frac {1}{\sqrt {1-x^2}}=\sum_{n=0}^ \infty \frac{\binom{2 n}{n} }{4^n}x^{2n}$$ That is to say that $$I=\int \frac {\log (x)}{\sqrt {1-x^2}}=\sum_{n=0}^ \infty \frac{\binom{2 n}{n} }{4^n\,(2n+1)^2}\left((2n+1)\log(x)-1 \right)x^{2n+1}$$ $$I=x (\log (x)-1) \, _3F_2\left(\frac{1}{2},\frac{1}{2},\frac{1}{2};\frac{3}{2},\frac{3}{2};x^2\right )+\frac{1}{9} x^3 \log (x) \, _3F_2\left(\frac{3}{2},\frac{3}{2},\frac{3}{2};\frac{5}{2},\frac{5}{2};x^2\right )$$

$\endgroup$
0
$\begingroup$

One does not need hypergeometric functions to find this antiderivative. It amounts to use poly-logarithms only. We have: \begin{eqnarray} \int \frac{\log(x)}{\sqrt{1-x^2}} dx &\underbrace{=}_{x=\sin(u)}& \int \log(\sin(u) du\\ &\underbrace{=}_{t=\exp(\imath u)}& \int \log(\frac{t-1/t}{2 \imath})\cdot \frac{dt}{\imath t}\\ &=& \int \frac{\log(t-1)+\log(t+1)-\log(2 \imath t)}{\imath t} dt\\ &=& \frac{1}{2} i \left(2 \text{Li}_2(-t)+2 \text{Li}_2(t)+\log ^2(2 i t)+2 \log (1-t) \log (t)-2 \log (t-1) \log (t)\right)\\ &=& \frac{1}{2} i \left(2 \text{Li}_2\left(-i x-\sqrt{1-x^2}\right)+2 \text{Li}_2\left(i x+\sqrt{1-x^2}\right)+2 \pi \arcsin(x)+\left(i \arcsin(x)+\frac{i \pi }{2}+\log (2)\right)^2\right) \end{eqnarray} In particular we have: \begin{equation} \int\limits_0^1 \frac{\log(x)}{\sqrt{1-x^2}} dx = -\frac{\pi}{2} \log(2) \end{equation}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.